2004
DOI: 10.1158/1078-0432.ccr-0754-03
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate (Gleevec) Inhibits Ovarian Cancer Cell Growth through a Mechanism Dependent on Platelet-Derived Growth Factor Receptor α and Akt Inactivation

Abstract: Purpose:We identified the platelet-derived growth factor receptor ␣ (PDGFR␣) as an ovarian cancer-specific gene by microarray hybridization using primary cultures. The purpose of this study is to evaluate whether disruption of the platelet-derived growth factor-regulated growth pathway by Imatinib mesylate (Gleevec), a partially selective PDGFR inhibitor, inhibits growth of ovarian cancer cells expressing PDGFR.Experimental Design: To investigate the effects of Imatinib mesylate in ovarian cancer, we establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 53 publications
4
87
1
2
Order By: Relevance
“…22 A recent study has demonstrated that imatinib mesylate inhibits ovarian cancer cell proliferation and PDGF-induced S-phase entry through PDGFR-a and Akt inactivation. 23 Although a phase II trial of imatinib mesylate as a single agent failed to produce satisfactory efficacy against recurrent and platinum-resistant ovarian cancer, 24 cases with clear-cell adenocarcinoma were not enrolled and, therefore, the effect of imatinib or other tyrosine kinase inhibitors on ovarian clear-cell adenocarcinoma remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent study has demonstrated that imatinib mesylate inhibits ovarian cancer cell proliferation and PDGF-induced S-phase entry through PDGFR-a and Akt inactivation. 23 Although a phase II trial of imatinib mesylate as a single agent failed to produce satisfactory efficacy against recurrent and platinum-resistant ovarian cancer, 24 cases with clear-cell adenocarcinoma were not enrolled and, therefore, the effect of imatinib or other tyrosine kinase inhibitors on ovarian clear-cell adenocarcinoma remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…2). [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Several types of cancers, particularly those derived from the ovary, prostate, breast, lung, brain, skin, and bone, express PDGFRa on the malignant cells themselves (Table 1). 22 In 1 experiment in which a human tumor array was probed with a cross-reactive polyclonal rabbit antibody to PDGFRa, PDGFRa expression was noted in approximately 95% of osteosarcomas and chondrosarcomas, in 77% of prostate cancers, in 52% of ovarian cancers, in 65% of breast cancers, and in 51% of lung cancers (N. Loizos, ImClone Systems, unpublished results).…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
“…Blocking VEGF prunes immature vessels, increases fraction of pericyte-covered vessels, and decreases vessel permeability, dilation and tortuosity Willett et al, 2004;Jain, 2005). Inhibition of PDGF or PDGFRb also prunes immature vessels, and additionally decreases contraction of the interstitial space and proliferation of stroma (Heuchel et al, 1999;Pietras et al, 2001;George, 2003;Matei et al, 2004;Vlahovic et al, 2006). Imatinib (Gleevec, Novartis Pharmaceuticals Corp., East Hanover, NJ, USA) is a synthetic small molecule that inhibits phosphorylation of a number of tyrosine kinase receptors including PDGFR, c-kit, and bcr-abl (Buchdunger et al, 1995;George, 2003;Matei et al, 2004).…”
mentioning
confidence: 99%
“…Inhibition of PDGF or PDGFRb also prunes immature vessels, and additionally decreases contraction of the interstitial space and proliferation of stroma (Heuchel et al, 1999;Pietras et al, 2001;George, 2003;Matei et al, 2004;Vlahovic et al, 2006). Imatinib (Gleevec, Novartis Pharmaceuticals Corp., East Hanover, NJ, USA) is a synthetic small molecule that inhibits phosphorylation of a number of tyrosine kinase receptors including PDGFR, c-kit, and bcr-abl (Buchdunger et al, 1995;George, 2003;Matei et al, 2004). It decreases proliferation of both tumour and stromal cells (George, 2003;Furuhashi et al, 2004;Kim et al, 2004;Matei et al, 2004;Ostman, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation